The Role of Didong Gayo in Instilling Religious Values and Morals in Early Childhood - Shaumiwaty, Shaumiwaty; Daulay, Sholihatul Hamidah; Shaulita, Rizkia; Faridah, Faridah (Corolla International Conference, 2023)
Didong is a traditional performing art originating from the Gayo tribe. Didong is used as a means to convey an expression of daily life. It contains messages for the younger generation. This kind of art greatly influences the people of Gayo community in their daily life, such as bringing enthusiasm to life. Interesting lyrics of the song are presented in the form of prose and rhyme that sounds funny in the Gayo community. Didong is usually performed on official occasions, such as weddings and regional holidays. The lyrics of Didong contain messages and advice related to religious, moral, and educational values that can become a strong foundation in early childhood. Didong aims to instill religious and moral values so that children are expected to behave well and politely as well as get used to worship. Children are expected to recognize monotheism through the Didong lyrics. Instilling religious and moral values in early childhood is one of the most important things in child development. This aims to lay a foundation of faith, such as taqwa to God, good character, confidence, and readiness to live in the middle of a society to lead a life that is pleasing to God.